THE EFFECT OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT ALFAMIDI PROSPERITY MINIMARKET OUTLET SOPPENG - Andi Asrijal; Rusnaedi; Irmawati (International Journal of Social Science, 2021)
The performance of an organization can be determined by the existence of a good organizational culture that exists within an organization. This work culture will not just appear, but must be pursued in earnest through a controlled process involving a controlled process involving all Human Resources (HR) in a set of systems, tools and supporting techniques. The objectives of the research carried out by the Alfamidi Prosperity Minimarket Outlet Soppeng are: to find out the description of organizational culture and employee performance at the Alfamidi Prosperity Soppeng Minimarket Outlet, Soppeng Regency. To answer these questions, the stages of the research method were used, starting from the literature review and field study, proposal preparation, testing the validity and reliability of the instrument, data collection, analysis and discussion. The data analysis used is descriptive quantitative. The results showed that the work culture of the employees at the Alfamidi Prosperity Minimarket Outlet Soppeng was high, as well as the employee performance at the Alfamidi Prosperity Soppeng Minimarket Outlet showed that the employee's performance was very good in achieving organizational goals.